2015
DOI: 10.1016/j.stem.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Normal and Alzheimer’s Disease Human Fibroblasts into Neuronal Cells by Small Molecules

Abstract: Neuronal conversion from human fibroblasts can be induced by lineage-specific transcription factors; however, the introduction of ectopic genes limits the therapeutic applications of such induced neurons (iNs). Here, we report that human fibroblasts can be directly converted into neuronal cells by a chemical cocktail of seven small molecules, bypassing a neural progenitor stage. These human chemical-induced neuronal cells (hciNs) resembled hiPSC-derived neurons and human iNs (hiNs) with respect to morphology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
485
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(499 citation statements)
references
References 30 publications
10
485
2
2
Order By: Relevance
“…On the contrary, no accumulation of tau protein was observed in this type of FAD-derived neurons, revealing that at least for that genotype this protein may not be the main cause of ailment [12,15,20]. Indeed, some studies have showed that iNs and iPSCs-derived neurons from FAD patient fibroblasts had an increased Aβ42/Aβ40 ratio that resembles that observed in AD brains [10,21,22]. Similarly, human iNs from familial AD patients recapitulated the pathology of altered processing and aberrant endosomal localization of APP as well as increased production of Aβ peptides [23].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…On the contrary, no accumulation of tau protein was observed in this type of FAD-derived neurons, revealing that at least for that genotype this protein may not be the main cause of ailment [12,15,20]. Indeed, some studies have showed that iNs and iPSCs-derived neurons from FAD patient fibroblasts had an increased Aβ42/Aβ40 ratio that resembles that observed in AD brains [10,21,22]. Similarly, human iNs from familial AD patients recapitulated the pathology of altered processing and aberrant endosomal localization of APP as well as increased production of Aβ peptides [23].…”
Section: Discussionmentioning
confidence: 70%
“…In this sense the use of small molecules seems to overcome those technical drawbacks being capable of converting human fibroblasts into neurons with a cocktail of small molecules supplemented with chemicals known to promote the differentiation of neural progenitors into neurons [9]. iNs produced by this cocktail possess typical functional hallmarks of neurons [10]. Recently, the application of stem cell research to neurodegenerative disorders is rapidly increasing, not only for cell replacement therapy [11] but also as potential models of the malady in vitro [12,13] contributing to improve knowledge of the cellular and molecular mechanisms of neurodegeneration and innovative drug discovery such as AD.…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, manipulation of these and other pathways is indeed sufficient to convert fibroblasts (mouse and human) and astrocytes (human) into neurons (Hu et al, 2015;Zhang et al, 2015).…”
Section: Direct Neuronal Reprogramming: Learning From Developmentmentioning
confidence: 99%
“…Neuronal conversion of human astrocytes and fibroblasts mediated by small molecules seems to require sequential phases of reprogramming, or a first phase of neuronal fate induction followed by a second phase of neuronal maturation (Table 1; Hu et al, 2015;Zhang et al, 2015). This strict order suggests some degree of organization in the molecular cascades involved in reprogramming that may recapitulate a developmental programme.…”
Section: Direct Neuronal Reprogramming: Learning From Developmentmentioning
confidence: 99%
“…In keeping, the small molecule-based reprogramming has attracted much interest due to its safety and efficiency in controlling cell fates (12); this methodology has been successfully used for fibroblast reprogramming into iPS or neurons (13). In this context, the recent paper by Wang et al described a novel approach to generate human induced endodermal progenitor cells (hiEndoPCs); the lineage reprogramming of gastrointestinal epithelial cells was obtained using a cocktail of defined small molecules in association with the support of tissuespecific mesenchymal feeders (1).…”
Section: Editorialmentioning
confidence: 99%